Safety and efficacy of BAY 81‐8973 for surgery in previously treated patients with haemophilia A: results of the LEOPOLD clinical trial programme. (1st March 2016) - Oldenburg, J.; Windyga, J.; Hampton, K.; Lalezari, S.; Tseneklidou‐Stoeter, D.; Beckmann, H.; Maas Enriquez, M.
Abstract : Introduction: BAY 81‐8973 is a recombinant factor VIII (rFVIII) with the same amino acid sequence as Bayer's sucrose‐formulated rFVIII (rFVIII‐FS) but manufactured with certain more advanced technologies. Aim: To describe surgery outcomes with BAY 81‐8973 in the LEOPOLD trials. Methods: Male patients with severe haemophilia A and no inhibitors aged 12–65 years with ≥150 exposure days (EDs) to FVIII (LEOPOLD I and II), or aged ≤12 years with ≥50 EDs to FVIII (LEOPOLD Kids), received BAY 81‐8973 based on dosing recommendations for rFVIII‐FS according to surgical requirements. Haemostasis‐related complications, investigator/surgeon assessment of haemostasis, blood loss, need for transfusion and use of BAY 81‐8973 were determined. Results: In LEOPOLD I and II, 11 patients (mean age, 35.3 years) underwent 13 major surgeries. In LEOPOLD Kids, one patient (aged 6 years) underwent one major surgery. Thirty‐two adult and paediatric patients underwent 46 minor surgeries. Haemostasis was rated good or excellent in all major and minor surgeries. Blood loss during surgery did not exceed expected amounts; blood transfusions were required in three of the 14 major surgeries. For major surgeries in LEOPOLD I and II, patients received a presurgical 50‐IU kg −1 dose of BAY 81‐8973; median nominal dose on day of surgery was 7000 IU (107.5 IU kg −1 ). Total BAY 81‐8973 dose was 2500 IU (108.7 IU kg −1 ) on the day of the only major surgery in LEOPOLD Kids. No haemostasis‐related complications were reported. Conclusions: Haemostatic control with BAY 81‐8973 during all surgeries in the LEOPOLD trials was good or excellent, with no haemostasis‐related complications.